Sistem Pakar Diagnosa Penyakit Lambung Berbasis Website Menggunakan Metode Forward Chaining & Certainty Factor - Sahay, Abertun Sagit; Fitriah, Andi Nurul; Christian, Efrans (Universitas Palangka Raya, 2021)
Gastric disease is a disease that cannot be underestimated, because if left unchecked it can result in other diseases appearing and can also cause death if not treated immediately. Diseases of the stomach can be caused by an inappropriate diet, a burden on the mind and also infections caused by bacteria. The little public knowledge of the early symptoms of gastric disease is the author's background to create a system that helps the public in obtaining information, consultation or initial treatment for gastric diseases without having to meet in person. The ability of an expert who can diagnose stomach diseases can be implemented into an application system. The methodology used in making the Gastric Disease Diagnosis Expert System Website is waterfall, namely analysis, design, implementation and testing. The testing phase focuses on the functional specifications of the program. In this Expert System, it uses the Forward Chaining method as reasoning and the Certainty Factor method to calculate the results of the yield trust. Hasil testing shows that this website can perform its function to diagnose gastric diseases. The test results are obtained from the inputs made by visitors by selecting the options that have been given and then will get the test results.